Réflexions critiques autour des frontières de la péninsule Ibérique au premier âge du Fer - Vanessa Rodrigues (Frontière·s)
Based on the archaeological register, the study of ethnicity and cultural identity in protohistoric societies, characterized by the absence of writing, always retains a partial and problematic character. The traditional approach has been to map some remains in order to recognize cultural areas that may coincide with the ethnic territories described by greco-latin literature. F. Barth denounced the approach of ethnic categories based on their cultural content to favour study of their boundaries. The identity of a particular group, he says, is shaped by interaction with others through a process inseparable from the existence of an ethnic boundary. It is therefore essential to question in Archaeology the theoretical transition between the notion of material culture and style and the identification of cultural spaces. After noting the nonsense of the protohistoric boundary perceived as separation, I will emphasize how the delimitation of study areas determines its approach. This article is then an opportunity to imagine other frontiers starting from the study of the appearance and the clothing fact in the Iberian peninsula in the Iron Age.